Islamic Financial Intermediation Compared to Ribaoui Financial Intermediation: A Theoretical and Mathematical Analysis - Khaldi, Khadidja; Hamdouni, Amina (International Journal of Economics and Financial Issues, 2018)
The present research uses mathematical analysis instruments for a comparative study between the Islamic financing system and the Ribaoui financing system usually called the classical financing scheme. The former system deals with contracts based on variable returns while the second i-e the ribaoui system is based on fixed return contracts. Using the principles of partial equilibrium theory for risk adverse investors, the study demonstrates that returns are higher with contracts based on profit and loss sharing. Keywords: Interest Rate, Classic Bank, Islamic Bank, Profit Sharing System, Return, Speculation, Mathematical Modelling. JEL Classifications: G21, G3